2010
DOI: 10.1186/1471-2180-10-134
|View full text |Cite
|
Sign up to set email alerts
|

Species specificity, surface exposure, protein expression, immunogenicity, and participation in biofilm formation of Porphyromonas gingivalis HmuY

Abstract: BackgroundPorphyromonas gingivalis is a major etiological agent of chronic periodontitis. The aim of this study was to examine the species specificity, surface exposure, protein expression, immunogenicity, and participation in biofilm formation of the P. gingivalis heme-binding protein HmuY.ResultsHmuY is a unique protein of P. gingivalis since only low amino-acid sequence homology has been found to proteins encoded in other species. It is exposed on the cell surface and highly abundant in the outer membrane o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
89
0
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 73 publications
(99 citation statements)
references
References 51 publications
2
89
0
8
Order By: Relevance
“…It has been shown that Bacteroides spp. can grow in and subsequently incorporate deuteroheme and mesoheme into a functional b-type cytochrome (McCall and Caldwell 1977;Fuller and Caldwell 1982), and that versatility in tetrapyrrole utilization may be a common feature within the phylum Bacteroidetes (Olczak et al 2010). Also, PPIX supports planktonic growth of P. gingivalis in basal medium (data not shown), similar to some non-iron metalloporphyrins examined (Fig.…”
mentioning
confidence: 61%
See 2 more Smart Citations
“…It has been shown that Bacteroides spp. can grow in and subsequently incorporate deuteroheme and mesoheme into a functional b-type cytochrome (McCall and Caldwell 1977;Fuller and Caldwell 1982), and that versatility in tetrapyrrole utilization may be a common feature within the phylum Bacteroidetes (Olczak et al 2010). Also, PPIX supports planktonic growth of P. gingivalis in basal medium (data not shown), similar to some non-iron metalloporphyrins examined (Fig.…”
mentioning
confidence: 61%
“…The best characterized heme acquisition system comprises the HmuR and HmuY proteins. HmuR is an outer-membrane TonB-dependent receptor engaged in heme transport through the outer membrane (Olczak et al 2001), whereas HmuY is a membrane-associated heme-binding lipoprotein (Olczak et al 2008(Olczak et al , 2010, which also binds iron(III) mesoporphyrin IX (mesoheme) and iron(III) deuteroporphyrin IX (deuteroheme) (Wojaczynski et al 2011). Detailed characterization of the HmuY-heme complex has revealed a unique protein all-beta fold structure in which histidines 134 and 166 bind heme in a low-spin Fe(III) hexa-coordinate arrangement (Wojtowicz et al 2009a, b).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The absorbance (OD 600 ) of cultures at given times was measured using a Genesys spectrometer (Thermo Scientific, Waltham, MA). Biofilm formation was measured as previously described (24,46,77) with slight modifications. Briefly, Pg83 and ⌬PG352 strains were grown to mid-log phase, and then the cell densities (OD 600 ) were measured to ensure that the same amounts of Pg83 and ⌬PG352 cells were used for biofilm measurements.…”
Section: Methodsmentioning
confidence: 99%
“…The assay was carried out in 96-well microtiter plates as previously described (24,46). The upper panel shows representative wells of Pg83 and the ⌬PG352 mutant, and the lower panel gives the average absorbances of Pg83 and the mutant.…”
Section: Figmentioning
confidence: 99%